Monitoring Cancer Outcomes Across the Continuum Data Synthesis and Analysis for the District of Columbia - Price, Rebecca Anhang (RAND Corporation, 2012)
This report synthesizes and analyzes available data regarding cancer-related outcomes among District of Columbia residents, highlighting key findings and data gaps across the continuum of cancer prevention, treatment, and outcomes and noting variability across subgroups of District residents.